The Neuromuscular, Biochemical, and Endocrine Responses to a Single-Session Vs. Double-Session Training Day in Elite Athletes - Kilduff, Liam (Journal of Strength and Conditioning Research, 2016)
The aim of this study was to compare the acute neuromuscular, biochemical, and endocrine responses of a training day consisting of a speed session only with performing a speed-and-weights training session on the same day. Fifteen men who were academy-level rugby players completed 2 protocols in a randomized order. The speed-only protocol involved performing 6 maximal effort repetitions of 50-m running sprints with 5 minutes of recovery between each sprint, whereas the speed-and-weights protocol involved the same sprinting session but was followed 2 hours later by a lower-body weights session consisting of 4 sets of 5 backsquats and Romanian deadlift at 85% one repetition maximum. Testosterone, cortisol, creatine kinase, lactate, and perceived muscle soreness were determined immediately before, immediately after, 2 hours after, and 24 hours after both the protocols. Peak power, relative peak power, jump height, and average rate of force development were determined from a countermovement jump (CMJ) at the same time points. After 24-hours, muscle soreness was significantly higher after the speed-and-weights protocol compared with the speed-only protocol (effect size η2 = 0.253, F = 4.750, p ≤ 0.05). There was no significant difference between any of the CMJ variables at any of the posttraining time points. Likewise, creatine kinase, testosterone, and cortisol were unaffected by the addition of a weight-training session. These data indicate that the addition of a weight-training session 2 hours after a speed session, whereas increasing the perception of fatigue the next day does not result in a difference in endocrine response or in neuromuscular capability.